2017
DOI: 10.15446/acag.v66n2.55026
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Ecuador is the most important exporter of canned peach palm, however, to date ideal soil fertility characteristics for peach palm growers remain unknown. The aim of this research was to determine optimal levels of soil nutrients for the cultivation of peach palm, specifically with regards to soil cation exchange capacity in order to obtain higher yields. We worked with 20 farmsteads and their soils from the province of Santo Domingo de los Tsáchilas during the second half of 2014. Fields were evaluated based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…This could be as a result of leaching due to high intensity of rainfall and the parent materials that are inherently poor in weatherable cation-yielding minerals in addition to the preponderance of low activity clays of the soils. Calcium levels are generally below the minimum requirement of 3.8 cmol/kg in almost all the soils (Quezada-Crespo et al, 2017). The micro-nutrients (Fe and Zn) are at sufficiency level only at the top soil.…”
Section: Soil Classification and Land Characteristicsmentioning
confidence: 90%
See 2 more Smart Citations
“…This could be as a result of leaching due to high intensity of rainfall and the parent materials that are inherently poor in weatherable cation-yielding minerals in addition to the preponderance of low activity clays of the soils. Calcium levels are generally below the minimum requirement of 3.8 cmol/kg in almost all the soils (Quezada-Crespo et al, 2017). The micro-nutrients (Fe and Zn) are at sufficiency level only at the top soil.…”
Section: Soil Classification and Land Characteristicsmentioning
confidence: 90%
“…The chemical properties revealed that a available P is generally deficient as none of the pedons contains the required critical level of 15 mg/kg (Fernandes and Soratto, 2012) for sustainable arable cropping. The soils are also low in potassium, with values of K ranging from 0.13 cmol/kg at the surface in Dodokindo Series to 0.31 cmol/kg at both Atan and Pakoto Series' which are just within the lower limits of the critical level of 0.2 -2.6 cmol/kg (Quezada-Crespo et al 2017). Effective Cation Exchange Capacity is above the critical value of 5.0 cmol/kg observed by Quezada-Crespo et al (2017) in Dodokindo and Owode Series but are lower in the other soil types.…”
Section: Soil Classification and Land Characteristicsmentioning
confidence: 92%
See 1 more Smart Citation
“…The ECEC values of the soils are above the minimum standard of 4.0 cmol/kg in all portions of the land area owing principally Orimoloye et al 91 to Calcium levels that are generally higher than the minimum requirement of 3.8 cmol/kg in all the soils. These according to Crespo et al (2017) are dependent on such parameters as pH and organic matter content of the soils. The organic carbon levels of the soils are low ranging from 1.1 to 2.68 g/kg which is far below the critical level of 30 g/kg proposed by ISRIC (1995).…”
Section: Discussionmentioning
confidence: 99%
“…Their critical values are 20 to 25, 1.2 to 2.0 and 3.0 to 3.45 mg/kg, respectively. The iron (Fe) content of the soils are however very high, far above the critical value of 161 mg/kg (Feiziasl et al, 2009;Crespo et al, 2017). Those nutrient elements that are below the critical levels need be supplied through deliberate fertilizer application to build up their levels in the soil.…”
Section: Discussionmentioning
confidence: 99%